The Mediating Effect of Knowledge Integration on the Relationship between Capability and Innovative Behaviour - Suthiluk Lapsomboonkamol; Noawanit Songkram; Pattarporn Thamsuwan; Nutthakorn Songkram (Emerging Science Journal, 2022)
One of the main success drivers of the Fourth Industrial Revolution is the integration of information technology and industry, which encourages innovation through collaboration between industry and academia. As a result, fostering innovative behaviour among undergraduates is essential for success in higher education throughout this revolution. The purpose of this study is to examine the direct effects of capability (leadership, technological literacy, interaction, knowledge sharing, and collaboration) on innovative behaviour and the indirect effect of knowledge integration's mediating role. Data from 3,230 undergraduates was collected and analysed. The provided hypotheses were validated using structural equation modelling, which demonstrated that capability significantly influenced the success of adopting innovative behaviour. Furthermore, we observed that knowledge sharing was the most powerful predictor. We also discovered that the intervening knowledge integration had an indirect effect, indicating the presence of a relationship between capability and innovative behaviour through this variable. When the direct and indirect effects were evaluated, the direct effect was substantially stronger than the indirect effect. The study's practical implications should focus strongly on promoting innovative behaviour and knowledge integration in the process of establishing appropriate educational programmes for universities. Furthermore, universities should develop strategies to encourage undergraduate students to share their knowledge and abilities with others since this improves performance and increases awareness of new prospects for innovation. In future research, we should include more educational institutions in our study, such as high schools, technical schools, and graduate students. Doi: 10.28991/ESJ-2022-SIED-07 Full Text: PDF